EDITORIAL (American Journal of Islam and Society, 1993)
This is the tenth year of the existence of AJISS. Starting from a publicationschedule of twice a year in 1984 to three times a year in 1989, itbecame a desk-topped quarterly in 1993. In 1992, due to increased demand,we began printing AJISS simultaneously in Washington, DC, andMalaysia. This year, it will also be published in Pakistan as well as translatedinto Turkish in Turkey, in shii. Allah. We are grateful to AlmightyAllah for our widespread readership and for the contributions sent fromaround the globe.In this issue, we feature two articles on various theoretical aspects ofthe Islamization of knowledge. The first one, by Ibrahim A. Ragab, discussestheory building in the Islamic social sciences. He argues for an alternativesocial science framework based on the Islamization paradigm,which he asserts could integrate both empirical and nonempirical elementsof behavior into a united system of explanation. Exploring the possibilityof using knowledge derived from revelation as a major source in the processof theory building, he encourages Muslim social scientists to drawupon the rich insights derived from the transcendental sources, but onlyafter subjecting the resulting propositions to stringent verification. Ragabassures us that this new model rejects unwanted dogmatism, unwarrantedexclusiveness, and a parochiality that shuns anything that comes by wayof non-Muslims. Muslim social scientists, he opines, will have to reorienttheir critical approach to their disciplines and also acquire a better understandingof the religious sciences: revealed knowledge. This would ensurea Muslim contribution in the social sciences, a contribution that disappearedduring centuries of stagnation in the Islamic ummah.In the second paper, Louay Safi examines the progress of the Islamizationof knowledge project over the last decade. He outlines the generalframework, analyzes the work of its proponents and critics (al Faruqi, alBuff, Rahman, 'AbuSulayman, Arif, Umziyan, Abul-Fadl), and proposesmodifications aimed at overcoming the difficulties inherent in the originalplan. Safi makes it clear at the outset that even though the production of ...